Forlis Gaiman: Project to improve the scientific writing skills of Islamic Religious Education teachers in Sleman Regency - Mohamad Joko Susilo (Contemporary Education and Community Engagement (CECE), 2026)
Efforts to improve teacher competence in writing scientific papers need to be continuously honed and improved because teachers' inability to write scientific papers has an impact on various things including career advancement. This community service aims to improve the motivation and writing skills of scientific papers of teachers in Sleman Regency through the Sleman Islamic Religious Teacher Writing Forum (Forlis Gaiman). This community service activity was organized by the Islamic Studies Department, Faculty of Islamic Religious Sciences, Islamic University of Indonesia targeting 24 State Islamic Religious Education teachers in Sleman Regency. The activity was packaged as a 2-day training on November 5-6, 2022, at the FIAI Postgraduate Campus. In addition to presenting the material, participants were also assigned to compile scientific journal articles. Based on the results of this community service, it can be seen that the various answers of training participants when asked about their motivation to take part in the training were mostly so that they could compile proposals and understand classroom action research. Other motivations for each individual are different depending on their own interests. The understanding of the material increased after being given the training treatment. Training participants also wrote scientific papers in the form of journal articles and carried out guidance, although less intensively. Overall, this activity is considered very important. The training participants felt happy, challenged to immediately prepare a proposal, and were satisfied based on the impressions of the training participants.